2014
DOI: 10.1002/dc.23130
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between conventional and liquid‐based cytology in screening for anal intraepithelial lesions in HIV‐positive patients

Abstract: Anal intraepithelial neoplasia (AIN) is associated with HPV infection and can be detected by cytological screening. While conventional exfoliative cytology (CC) is a low-cost and nonaggressive method, liquid-based cytology (LBC) tends to give clearer readings. Although studies of the efficacy of anal cancer screening methods would be of great importance for groups at high risk for AIN, few such studies have been conducted. The aim of the present study was to assess the concordance of CC and LBC in diagnosing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
1
10
0
4
Order By: Relevance
“…Twenty-one studies described cytology [22–41, 43]. Seventeen described liquid-based cytology [22–31, 33, 35, 38–41, 43], 3 conventional cytology [32, 36, 37] and 1 both conventional and liquid-based cytology [34]. Eleven studies described HR-HPV DNA detection [23–25, 27, 30, 31, 33, 38–40, 43], 3 HPV E6/E7 mRNA analysis [38, 40, 44], 3 p16INK4a immunostaining [38, 39, 42], and 1 p16INK4a/Ki-67 dual staining [41].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies described cytology [22–41, 43]. Seventeen described liquid-based cytology [22–31, 33, 35, 38–41, 43], 3 conventional cytology [32, 36, 37] and 1 both conventional and liquid-based cytology [34]. Eleven studies described HR-HPV DNA detection [23–25, 27, 30, 31, 33, 38–40, 43], 3 HPV E6/E7 mRNA analysis [38, 40, 44], 3 p16INK4a immunostaining [38, 39, 42], and 1 p16INK4a/Ki-67 dual staining [41].…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators have reported that liquid-based preparations increase cell yield and reduce compromising factors such as obscuring fecal material, air-drying, and mechanical artifacts [ 31 , 32 ]. Others report that conventional and liquid-based cytology are equally effective in screening for ASIL [ 33 ]. Self-collection of anal cytology has also been investigated; in a community-based study of MSM, 80 % of men with limited or no experience with anal cytology screening were able to collect a sample on the fi rst attempt that was suffi cient for interpretation by a pathologist [ 34 ].…”
Section: Samplingmentioning
confidence: 97%
“…Several studies compared both techniques used in anal cytology [31][32][33]. Liquid-based cytology can reduce fecal and bacterial contamination and air-drying artifacts [31].…”
Section: Conventional Smears and Liquid-based Cytologymentioning
confidence: 99%
“…In that case, ThinPrep samples proved to be satisfactory twice as often as conventional smears (p < 0.005) and detected nearly eight times as many squamous intraepithelial lesions (p < 0.005). In a study by Maia et al [33], which included 33 HIV-positive patients who submitted to both an anal cytology and high-resolution anoscopy, conventional cytology identified 75% of patients with a positive biopsy, while liquid-based cytology identified 86% of these patients.…”
Section: Conventional Smears and Liquid-based Cytologymentioning
confidence: 99%